2012
DOI: 10.3189/2012jog11j163
|View full text |Cite
|
Sign up to set email alerts
|

Variational assimilation of albedo in a snowpack model and reconstruction of the spatial mass-balance distribution of an alpine glacier

Abstract: ABSTRACT. Accurate knowledge of the spatial distribution of the mass balance of temperate glaciers is essential for a better understanding of the physical processes controlling the mass balance and for the monitoring of water resources. In relation to albedo variations, the shortwave radiation budget is a controlling variable of the surface energy balance of glaciers. Remotely sensed albedo observations are here assimilated in a snowpack model to improve the modeling of the spatial distribution of the glacier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 56 publications
(86 reference statements)
3
49
0
1
Order By: Relevance
“…These results further stress the significance of the albedo on the mass balance of this kind of alpine glaciers (Dumont et al, 2012). The strong linear correlation shown in Fig.…”
Section: Albedo and Mass Balancesupporting
confidence: 72%
“…These results further stress the significance of the albedo on the mass balance of this kind of alpine glaciers (Dumont et al, 2012). The strong linear correlation shown in Fig.…”
Section: Albedo and Mass Balancesupporting
confidence: 72%
“…This is significant because the implementation of the most promising advances in simulation is mainly considered for distributed simulations. This is the case for assimilation of satellite data [44][45][46]; the inclusion of small scale processes in simulations, including snow redistribution by wind [30,32]; and gravitational or topographic controls on snow movements [29,47,48]. Semi-distributed simulations may also allow the implementation of satellite data assimilation techniques (as suggested in [49]) but would require specific methods for aggregating observations into the semi-distributed clustering of the simulation domain and they would reduce potential benefits of high resolution satellite observations.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been few examples of direct assimilation of satellite data into models of such a degree of complexity (Toure et al, 2011). Dumont et al (2012) have recently demonstrated how remotely sensed spectral albedo of snow can be assimilated into the detailed snowpack model Crocus, with positive impact on the simulated mass balance of an alpine glacier. Regardless of the frequency range (microwave, visible/near infrared, thermal infrared, .…”
Section: A Mary Et Al: Mountain Snow Ssa From Modismentioning
confidence: 99%